Preparation, characterization, and evaluation of sorghum flour with increased resistant starch content - Vu, Thanh Hien Thi (Kansas State University, 2014)
Sorghum flour is a gluten-free ingredient and can be used to prepare foods for celiac patients. In addition, sorghum flour is a good source of fiber in the form of resistant starch. The objectives of this research were to develop an effective process to increase resistant starch content of sorghum flour and investigate the effects of sorghum protein matrix on starch digestibility. Samples of white sorghum flour (28.9% amylose content) with different moisture contents (0%, 12.5%, 20%, and 30%) were treated at different temperatures (100, 120, and 140 [degrees]C) for different times (1, 2, and 4 h). Samples after heat treatments were tested for starch digestibility, protein digestibility, differential scanning calorimetry (DSC), size-exclusion chromatography (SEC), and X-ray diffraction. The sample treated with 20% moisture at 100[degrees]C for 4 h had high resistant starch (RS) content (22.1% compared with 5.6% of the native sample) and low protein digestibility (8.4% compared with 68.3% of the native sample). The same heat-moisture treatment on isolated sorghum starch showed no significant change in RS content. DSC showed a very low degree of gelatinization for samples treated at moisture contents 20% and below. X-ray diffraction also suggested minimal change in starch crystallinity after heat treatment at low moisture contents (20% and below). Sorghum protein solubility after heat treatment was reduced, suggesting that protein structure was altered during the heat treatments. In conclusion, heat-moisture treatments were successful in increasing resistant starch content of sorghum flour by altering sorghum protein without gelatinizing the starch to retain starch functionality in food product applications. Sorghum flour with increased resistant starch content after heat treatment was evaluated and compared with normal sorghum flour for starch digestibility using the Integrated Total Dietary Fiber method, and for food applications in tortillas.
Keywords: Resistant starch; Sorghum flour; Heat-moisture treatment